Tires-road forces estimation: Using sliding mode and triangular observer. (30th March 2019) - Hamadi, Nacer; Imine, Hocine; Ameddah, Djamel-eddine; Chari, Abdelhamid
Abstract: This paper presents two kinds of observers: first order sliding mode and triangular form, applied to a dynamic model of a vehicle in order to estimate the dynamic state of the vehicle and contact forces. The vehicle model is based on Lagrange formalism, which takes into account the evolution of each subsystem under normal operation when there is a possible presence of defects. Within this work, the obtained results are represented with an illustration of the absolute errors between the two methods compared to the simulation results.